Management Optimization Tourism Business Unit at BUMDES Dharma Abadi in Apuan Village, Kec. Susut, District. Bangli - Ni Made Puspasutari Ujianti; Ida Ayu Putu Widiati; Luh Putu Suryani; Ni Made Wahyuni; Dewa Gede Agung Semarabawa; I Wayan Sunarta; Ni Putu Laksmi Krisnina Maharani; Ida Ayu Kartika Indrawan (Fakultas Hukum, Universitas Warmadewa, 2024)
Apuan Village is one of the villages in Susut District, Bangli Regency, which has many potential water tourism attractions in the form of waterfalls, rivers and baths. In accordance with the provisions of Law Number 6 of 2014 concerning Villages, it is stipulated that an entity called a Village-Owned Enterprise, each village may have a Business Entity to manage the village's potential through its business units. BUMDes Dharma Abadi, is a business entity owned by Apuan village which was founded in 2017, with several business units. The business units managed by BUMDes Dharma Abadi are savings and loan business units, drinking water supply management and Tibumana tourist attraction management. The Tibumana tourist attraction management business unit still cannot be optimally developed, this occurs due to a lack of management capability from the human resources it has, so the development of the business unit managed by BUMDes which is expected to be able to improve community welfare and also be able to increase the APuan Village PADes cannot be achieved. achieved.